Exploring the gap between what we say and what we do: Writing centres, ‘safety’, and ‘risk’ in higher education - Clarence, Sherran (Stellenbosch Papers in Linguistics Plus, 2019)
Writing centres are a well-established aspect of student academic support in many universities around the world. As much as there is significant commonality in their espoused ways of working, and theoretical and ontological underpinnings, writing centres work in a diverse range of national and institutional contexts. At times, the pressures from their contexts – both ideological and practical – can work to shape the day-to-day nature of writing centre work that moves away from, rather than towards, their espoused ways of working. This gap between “theory” and “practice” in writing centres is the focus of this paper. The paper argues that acknowledging and characterising the nature of this gap in different writing centre contexts is vital, and needs to be taken on honestly and critically. This may better enable writing centres to act more consciously as a “critical conscience” in university spaces increasingly vulnerable to narrow, uncritical notions of ‘safe’ spaces for student development and growth.